PENGARUH MODAL, PENGALAMAN USAHA, DAN JAM KERJA TERHADAP PRODUKTIVITAS PETERNAK SAPI POTONG DI KECAMATAN KUTA UTARA KABUPATEN BADUNG - Kusuma, I Made Pranata; Wenagama, Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
This study aims to determine the effect of capital, business expirience, and working hours on the productivity of beef cattle breeders. This research was conducted in North Kuta District, Badung Regency using total sampling and data collection methods of non-participant observation and semi-structured interviews. The analysis technique used is multiple linear regression analysis. The results obtained are that simultaneously all independent variables have a positive and significant effect on the dependent variable. Partially the variables of capital and business experience have a positive significant effect and the variable working hours has a positive but not significant effect on the productivity of beef cattle breeders in North Kuta District, Badung Regency. The implication of the result of this study is as a real source of information for the government regarding the productivity of beef cattle breeders in North Kuta District, Badung Regency.